Faktor Penyebab dan Upaya Penanggulangan Tindak Pidana Penggelapan Kepemilikan Hak Atas Tanah: (Studi di Desa Pilohayanga) - Azelchie Caroline; Lisnawaty W. Badu; Nuvazria Achir (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
This research aims to analyze the factors that cause criminal acts of embezzlement of ownership of land rights. The research method used in this research is empirical legal research using data collection techniques through direct observation and interviews with the litigants. The results of the research show that the factors that cause criminal acts of embezzlement of ownership of land rights include economic factors, lack of the concern of land owners regarding the wealth they own, the ignorance of the victim's heirs regarding land ownership, the current high price of land has resulted in people starting to look for their land, as well as the factor of selling or exchanging land at that time using a belief system, resulting in the transfer of land rights. there is no evidence of the land. Overcoming criminal acts of embezzlement of ownership of land rights in three ways: preemptive efforts, preventive efforts and repressive efforts, namely by taking more potential steps to avoid conflicts in the land sector..